Tobacco consumption in Spain: Individual risk profiles - Nieto-González, Imanol L.; Rodríguez-Donate, M. Carolina; Guirao-Pérez, Ginés (Tobacco induced diseases, 2023)
The aim of this study is to identify profiles of never smokers, ex-smokers, occasional smokers, and daily smokers, through their individual, lifestyle, and health characteristics. This analysis allows provides profiles of individuals with a greater or less propensity to use tobacco, which contributes to the design of effective prevention policies. Econometric models are used with data from the Spanish National Health Survey. Specifically, a multinomial logit model is estimated to evaluate the probabilities of tobacco use. Additionally, discrete changes, odds ratios, and predicted probabilities for prone individuals, are calculated. Differences are found between the profiles of each alternative of tobacco use. The individual attributes with the most striking effect are being aged 26-45 years, which reduces the probability of being a non-smoker by 21 percentage points compared to the younger group, and regular exposure to secondhand smoke, which is 30% more likely to be a regular smoker. The characteristics that define an individual with higher probability of smoking daily are: belonging to a certain region of Spain, male, aged 26-45 years, born in Spain, unemployed, with primary studies, separated, no physical activity, consumes alcohol, and is exposed to smoke regularly, not chronically ill, and have very poor health. Identification of the profiles most likely to choose each of the tobacco consumption alternatives can contribute to the design of more effective prevention strategies. The results confirm that the accumulation of bad habits results in a high risk of smoking. The quantification of the differences in the effects of each trait is an interesting contribution that is useful to orient the policies to specific segments of the population more prone to consume tobacco.